“Adaptación escolar y desarrollo social. estudio en los niños del centro infantil del Buen Vivir “Francisco Chiriboga” Riobamba, período 2016.” - Robalino Barrera, Jéssica Pilar (2017)
This research was conducted at the CIBV (Centro Infantil del Buen Vivir) “Francisco Chiriboga”, with the purpose of finding solutions to one of the problems common in every institutions dealing with children. Adaptation to the formal education process is essential in children, since this process affects their cognition, independence and self-confidence. It was verified the need of a correct process of adaptation, so that children not only get the common abilities but also develop social skills. By reading this paper, readers will be able to learn about the systematic and planned school adaptation process proving it produces positive results on social development of 1-3 years old children. The methodology applied in the present investigation was observation technique, supported by the observation guide as instrument and it was applied to a population of 15 boys and 25 girls, with the scientific method supported by an inductive – deductive process. As conclusion, games, rounds and puppets directed to solve the school adaptive issue are appropriate and productive methods to achieve appropriate social development skills in the children of the CIBV “Francisco Chiriboga”. As support and contribution the Guide “Me Divierto y Socializo” was presented in which theory is put into practice. It includes motivational exercises that leads to activities that promote school adaptation and develops the social environment of children. Applying the School Adaptation Strategies Guide “Me Divierto y Socializo” using games, puppets and rounds statistically probed the Social Development of the Children of “ Francisco Chiriboga” Good Living Center” in Riobamba 2016 was improved.